自适应滤波技术在车辆变速箱故障诊断中的应用 - 乔新勇; 刘玮 (Jixie chuandong)
It is an effective method to diagnose the faults of gearbox through vibration measure. But usually the measured vibration signal is disturbed by the vibration of the other parts of vehicle when measure is taken on the vehicle. The gear tooth broken fault on the gearbox of armored vehicle is simulated. The body vibration signals of gearbox and engine at the same time are measured. The noise caused by the vibration of engine through adaptive filtering from the vibration of gearbox is filtered,and vibration signal in time domain and also in frequency domain is analyzed. The frequency characteristic of vibration signal through Hilbert transformation is extracted. Diagnosis of the gear tooth broken fault of gearbox is realized.